TO THE PROBLEM OF INTEGRATION OF COMPUTER TECHNOLOGIES INTO THE PROCESS OF FOREIGN LANGUAGE STUDENTS - Galtsova, N.V. (Pedagogy of Higher and Secondary Education, 2010)
The necessity of the integration of modern information technologies is under consid eration in this article. It implies the creation of the necessary base for teaching English when there is a close cooperation between teachers and students.